2021
DOI: 10.1007/s12671-021-01692-8
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Versus Cognitive Reappraisal: the Impact of Mindfulness-Based Stress Reduction (MBSR) on the Early and Late Brain Potential Markers of Emotion Regulation

Abstract: Objectives A positive association between trait mindfulness and cognitive reappraisal has previously been found. Using event-related potentials (ERPs), we investigated the impact of an 8-week MBSR course on early and late stages of emotion regulation using mindfulness and reappraisal. Methods Participants were allocated into an 8-week MBSR training group (n = 14 for task reports and self-reports; n = 10 for ERPs) or a wait-list control group (n = 15 for ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
(106 reference statements)
3
10
0
Order By: Relevance
“…Another signature of the ERP sensitive to emotional processing examined in the present study was the centroparietal LPP, a component thought both to reflect the in-depth evaluation and motivational relevance of emotional stimuli, and be related to response preparation (Lang and Bradley, 2010;Yang et al, 2015;Kaunhoven and Dorjee, 2021). Our results showed that LPPs elicited by MA-related stimuli were significantly smaller than those elicited by negative or positive stimuli, whereas there was no significant difference between positive and negative stimuli.…”
Section: Discussionsupporting
confidence: 42%
“…Another signature of the ERP sensitive to emotional processing examined in the present study was the centroparietal LPP, a component thought both to reflect the in-depth evaluation and motivational relevance of emotional stimuli, and be related to response preparation (Lang and Bradley, 2010;Yang et al, 2015;Kaunhoven and Dorjee, 2021). Our results showed that LPPs elicited by MA-related stimuli were significantly smaller than those elicited by negative or positive stimuli, whereas there was no significant difference between positive and negative stimuli.…”
Section: Discussionsupporting
confidence: 42%
“… Among regression algorithms the usual choices are: linear regression [ 173 , 174 , 175 ], Lasso Regression [ 176 , 177 ], Logistic Regression [ 178 , 179 , 180 ], Multivariate Regression [ 181 , 182 ], and Multiple Regression Algorithm [ 183 , 184 ]. Among clustering algorithms the most common choices in biometrics or neuroscience research are: K-Means Clustering [ 185 , 186 , 187 ], Fuzzy C-means Algorithm [ 188 , 189 ], Expectation-Maximization (EM) Algorithm [ 190 ], and Hierarchical Clustering Algorithm [ 188 , 191 , 192 ]. Among reinforcement learning algorithms the most common choices are: deep reinforcement learning [ 193 , 194 , 195 ] and inverse reinforcement learning [ 196 ].…”
Section: Brain and Biometric Affect Sensorsmentioning
confidence: 99%
“…Among clustering algorithms the most common choices in biometrics or neuroscience research are: K-Means Clustering [ 185 , 186 , 187 ], Fuzzy C-means Algorithm [ 188 , 189 ], Expectation-Maximization (EM) Algorithm [ 190 ], and Hierarchical Clustering Algorithm [ 188 , 191 , 192 ].…”
Section: Brain and Biometric Affect Sensorsmentioning
confidence: 99%
“…For informative matters, the potential interrelatedness between mindfulness with its acceptance and emotional regulation through cognitive reappraisal may support students perceived abililties to reappraise emotional activating situations in a more optimistic manner. This should, as also suggested elsewhere, be further investigated Kaunhoven & Dorjee, 2021).…”
Section: Discussion Of the Main Findings Of The Qualitative Studymentioning
confidence: 57%
“…Mindfulness may further reduce emotional reactivity to situations perceived as threatening (Goldin & Gross, 2010;Kaunhoven & Dorjee, 2021) and support regulation of emotions through cognitive reappraisal by fostering a more realistic and possibly more optimistic perspective on the situation at hand. Mindfulness may thereby increase the individual's ability to refrain from automatic reactions to stimuli, and function as a resource to support coping (Kaunhoven & Dorjee, 2021) either directly or by supporting cognitive reappraisal of emotions by shifting the way one interprets situations (Garland et al, 2009). This aligns with research suggesting that mindfulness lowers students' perceptions of stress by altering emotions and increasing the timely processing, and thus regulation of, emotional signals related to school tasks .…”
Section: Mindfulnessmentioning
confidence: 99%